Impact of Store Atmosphere and Brand Loyalty on Repurchase Intentions: A Quantitative Study: Dampak Suasana Toko dan Loyalitas Merek terhadap Niat Pembelian Kembali: Sebuah Studi Kuantitatif. - Muzakki, Ilham; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the influence of store atmosphere and brand loyalty on repurchase intentions at a retail outlet. Utilizing a descriptive approach and quantitative methods, data was gathered from 96 respondents through purposive sampling and Google Forms questionnaires. The analysis, conducted using SPSS Statistics 22, revealed that store atmosphere and brand loyalty significantly affect repurchase intentions. These findings underscore the importance of creating a conducive store atmosphere and fostering brand loyalty to enhance customer repurchase intentions, offering valuable insights for marketers and retailers aiming to optimize customer retention strategies Highlights: The study employs quantitative methods to assess the impact of store atmosphere and brand loyalty on repurchase intentions. Findings confirm a significant influence of both store atmosphere and brand loyalty on customer repurchase intentions. This research provides valuable insights for marketers and retailers seeking to enhance customer retention strategies. Keywords: Store Atmosphere, Brand Loyalty, Repurchase Intentions, Quantitative Study, Customer Retention